2018
DOI: 10.3390/economies6040055
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does Economic Growth Contribute to Child Stunting Reductions?

Abstract: The role of economic growth in reducing child undernutrition remains an open and highly debated question that holds important implications for food security strategies. The empirical evidence has been quite contrasted, primarily in regard to the magnitude of the impacts. Yet, most studies have not (appropriately) accounted for the reverse causality between economic growth and child stunting. Using a dataset of 74 developing countries observed between 1984 and 2014, this paper develops a novel approach accounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 41 publications
(76 reference statements)
2
39
1
5
Order By: Relevance
“…[21] The annual income showed a significant positive association with stunting proving that the increase in income reduces poverty which, in turn, contribute to optimum growth of children. [22]…”
Section: Discussionmentioning
confidence: 99%
“…[21] The annual income showed a significant positive association with stunting proving that the increase in income reduces poverty which, in turn, contribute to optimum growth of children. [22]…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, the relationship between economic growth and child nutrition has attracted noteworthy research and donor attention 24–30. Using a data set of 74 developing countries observed between 1984 and 2014, many concluded that economic growth is not a sufficient condition for child undernutrition reductions,31 while others suggested that factors that contributed the most to the decrease in child stunting are full immunisation, iron supplements and deworming medication 32. Economic growth can lead to widening inequalities in a variety of ways, such as access to education, health and technology, and growth represents an important means to reduce poverty only if income distribution remains constant over time 29.…”
Section: Introductionmentioning
confidence: 99%
“…107 While this is in line with the findings of several studies, 108 others find that child stunting would be decreased even more, for example by 7.3 percent. 109 In contrast, still others find the relationship to be much weaker or even nonexistent. 110 The relationships between economic growth and child stunting can also differ by region.…”
Section: How Does Economic Growth Contribute To Nutrition?mentioning
confidence: 99%